Kekuatan Mengikat Dari Keputusan Arbitrase Dihubungkan Dengan Sifat Final & Binding - Erleni; Meidya Wulandari; Oktariani; Ocky Yogananta; Fery Arifandi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Contemporary business actors often use arbitration, a method of resolving disputes outside of court. Arbitrase di Indonesia diatur oleh Undang-Undang Nomor 30 Tahun 1999 tentang Arbitrase dan Penyelesaian Sengketa Alternatif. More and more cases are being registered with the Indonesian National Arbitration Board. Arbitrasi semakin penting dalam penyelesaian sengketa bisnis nasional dan internasional karena banyaknya kontrak bisnis atau perdagangan yang mencakup klausul arbitrase. Arbitration awards are final and binding, because arbitration follows the principle of final and binding. The decision immediately has permanent legal force from the moment it is pronounced because the arbitration decision is final and binding. Therefore, no further legal recourse can be taken against that decision. Article 70 provides the disputing parties with the opportunity to raise objections, while Article 60 states that the arbitration decision is final and has permanent legal force.